Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.yjmcc.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte cell cycle dynamics and proliferation revealed through cardiac-specific transgenesis of fluorescent ubiquitinated cell cycle indicator (FUCCI)

Abstract: Rationale: Understanding and manipulating the cardiomyocyte cell cycle has been the focus of decades of research, however the ultimate goal of activating mitotic activity in adult mammalian cardiomyocytes remains elusive and controversial. The relentless pursuit of controlling cardiomyocyte mitosis has been complicated and obfuscated by a multitude of indices used as evidence of cardiomyocyte cell cycle activity that lack clear identification of cardiomyocyte "proliferation" versus cell cycle progression, endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 65 publications
1
40
0
1
Order By: Relevance
“…However, recent studies have demonstrated a low but constant rate of cardiomyocyte turnover in the adult mammalian heart [46][47][48][49]. Newly generated cardiomyocytes originate from a subpopulation of pre-existing cardiomyocytes that retain their proliferative capacity throughout adulthood [19,22,[46][47][48][49][50]. Several studies have suggested that these may represent a population of cardiomyocyte progenitors [19,22,51,52].…”
Section: Polyploidization and Progenitor Proliferation In The Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have demonstrated a low but constant rate of cardiomyocyte turnover in the adult mammalian heart [46][47][48][49]. Newly generated cardiomyocytes originate from a subpopulation of pre-existing cardiomyocytes that retain their proliferative capacity throughout adulthood [19,22,[46][47][48][49][50]. Several studies have suggested that these may represent a population of cardiomyocyte progenitors [19,22,51,52].…”
Section: Polyploidization and Progenitor Proliferation In The Heartmentioning
confidence: 99%
“…As a result of this technology, cell cycle phase analysis performed contemporarily with the measurement of DNA content, can distinguish between diploid (4C) and polyploid (4C) cells in cell cultures or in organs [110]. This emerging technique has led to a significant recognition of the presence of polyploidy in several organs, and puts into question the classic concept about tissue growth during development and repair after injury [23,50,86].…”
Section: Cell Cycle Live Imagingmentioning
confidence: 99%
“…In comparison, percentage of cCICs retained in the adult infarcted heart at 48 hpi was significantly lower at 5.2% ± 1.0% (5192 ± 954; P < .0001) (Figure S4c) verifying higher fractional initial cell retention in neonatal vs a pathologically injured adult heart. Second, cell cycle activity of cCICs retained in the postnatal heart was assessed using fluorescence ubiquitination‐based cell cycle indicator (FUCCI) labeling (Figure A, see Section 4). FUCCI lentiviruses (cCIC FUCCI ) carrying cell cycle indicators Geminin + (Azami Green; AzG) and Cdt1 + (monomeric Kusabira Orange 2; mKO2) were used to transduce cCICs, and double‐positive cells were selected prior to intramyocardial injection by flow cytometric cell sorting (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…During G1/S transition, both probes are present, resulting in a yellow fluorescence (overlaid green and red); during the brief gap between M and G1 phases, neither probe is present and fluorescence is absent. Oscillation between red, yellow, and green signals tracks cell cycle status (Figure A). FUCCI lentiviral plasmids were generated as previously described .…”
Section: Methodsmentioning
confidence: 98%
“…In murine cardiomyocytes, previous studies have reported that rodent binucleation increases dramatically between postnatal day 4 and 12 56 and by adulthood, over 80% of single cardiomyocyte nuclei are diploid 57 . Recently, our group reported that postnatal day 2 cardiomyocytes demonstrate the highest number of cardiomyocytes in S/G2/M cell cycle phase during postnatal development 58 . Our study indicates approximately 40% of day 3 single nucleus DNA content of cardiomyocytes are polyploid, which sharply reduces to 15% by day 7 and maintained at 15% into adulthood ( Figure 2).…”
Section: Discussionmentioning
confidence: 98%